The Managing Director's Statement on the Role of the Fund in Addressing Climate Change. (Policy Papers; Policy Paper, 2015)
The Fund has a role to play in helping its members address those challenges of climate change for which fiscal and macroeconomic policies are an important component of the appropriate policy response. The greenhouse gas mitigation pledges submitted by over 160 countries ahead of the pivotal Climate Conference in Paris in December represent an important step by the international community towards containing the extent of global warming. Strategies for reducing emissions will reflect countries' differing initial positions, political constraints and circumstances. Carbon pricing can, however, play a critical role in meeting in the most efficient and effective way the commitments that countries are now entering into; it can also raise substantial revenues that can be used to reduce other, more distorting taxes. Through its incentive effects, carbon pricing will also help mobilize private finance for mitigation activities and spur the innovation needed to address climate challenges. Finance ministries have a key role to play in promoting and implementing these policies and ensuring efficient use of the revenue raised. The process of climate change is set to have a significant economic impact on many countries, with a large number of lower income countries being particularly at risk. Macroeconomic policies in these countries will need to be calibrated to accommodate more frequent weather shocks, including by building policy space to respond to shocks; infrastructure will need to be upgraded to enhance economic resilience. It will be important that developing countries seeking to make these adaptations have access to sufficient financial support on generous terms. Financial markets will play an important role in helping economic agents and governments in coping with climate change-induced shocks. And heightened climate vulnerabilities and the structural adjustments associated with a shift towards a low-carbon economy over the medium-term will have important implications for financial institutions and financial stability. This paper identifies areas in which the Fund has a contribution to make in supporting its members deal with the macroeconomic challenges of climate change, consistent with national circumstances. It draws on materials contained in a forthcoming Staff Discussion Note (Farid and others 2015) and has benefited from the discussions at informal Board meetings on IMF work on climate change held on September 30 and November 24, 2015.